Resolusi Sengketa Penarikan Sebagian Benda Wakaf oleh Ahli Waris Wakif Melalui Pendekatan Maqashid Al-Syari’ah Perspektif Hukum Positif - Mastri Imammusadin (Qonuni: Jurnal Hukum dan Pengkajian Islam, 2024)
Waqf land disputes are a widespread phenomenon in society. It is not uncommon for a lawsuit to be filed by the wakif himself, or by the wakif's heirs, so that the purpose of waqf as worship with social functions is often constrained. Not to mention the conflicts that can never be resolved because of the feeling of "ewuh-pekewuh" nadzir against wakif and his heirs. This research is an empirical juridical research on waqf land dispute cases with legal ethnography research that involves researchers in the dispute resolution process. This research describes the process of resolving a waqf land dispute whose lawsuit was filed by the heirs of the waqif and has been going on for almost 30 years. The purpose of this research is to find out the maqashid al-syari'ah approach used in the settlement of waqf disputes in the perspective of positive law. The subjects in this research are the parties involved in the dispute interviewed by the researcher, plus resource persons from the Land Office and the local MUI Fatwa Council. Based on the results of the research, it was found that the settlement of a quo dispute was in principle contrary to both positive law and shari'ah. However, through the maqashid al-syari'ah approach, the deviation can be justified for the sake of peaceful resolution of the dispute solely to maintain the establishment of religion (hifzd al-din).